Efficient catalytic hydrogen generation from formic acid dehydrogenation on ultrafine PdAu nanoparticles supported on modified carbon derived from rice straw - Qu, Jin; Wang, Hongli; Wang, Zelong; Zhang, Jingjing; Zhao, Zhankui (European physical journal. Applied physics, 2023)
Formic acid (FA) dehydrogenation at ambient conditions is a promising route for hydrogen (H 2 ) generation but still suffers from low activity and selectivity. Here, potassium hydroxide (KOH) and 3-aminopropyl triethoxysilane (APTES) modified porous carbon derived from the pyrolysis of rice straw (RSNPC) offers an effective support to promote the formation of ultrafine PdAu nanoparticles (NPs). Benefiting from the small sizes of PdAu NPs, the Pd 0.7 Au 0.3 /RSNPC catalyst exhibits excellent catalytic performance for FA dehydrogenation reaction with a high turnover frequency (TOF) of 6794.3 mol H 2 mol catalyst −1 h −1 at ambient conditions, outperforming most of reported catalysts for FA dehydrogenation under similar conditions.